Strategi Peningkatan Kualitas Lulusan Smk Melalui Konsep Cluster Bidang Keahlian Dan Sertifikasi Siswa - Taufik Hidayat (STAI Sangatta Kutai Timur, 2020)
This article present a strategy to improve the student graduate quality of vocational high school, with the concept the competence cluster area and student certification. The competence cluster area is a grouping of vocational high schools in each regency based on their competence, namely : Technology and Engineering competence area, consist of Industrial Mechanical Engineering, Welding, Ottomotive, Mining, Fisheries, Shipping, Cruising, Technology and Informatics. Business and Management competence area, consist of : Accounting, Office Administration, Marketing, Cullinary Art and Fashion. Agriculture and Agribusiness competence area, consist of : Agricultural Engineering, Food Crop Agribusiness, Horticultural Agribusiness and Agrotechnology. Health competence area, consist of : Nursing, Analytical chemistry and pharmacy. From four competence area above submitted as the best schools in their fields to become LSP P1, namely professional certification institute P1 and also as Competency Test place for students in their respective regions, with standard Professional Certification National Agency (BNSP) and also students who follow both public and private district will get a professional certificate issued by BNSP. So that, with formally the student graduate quality of Vocational high school in the region have the same standard that set BNSP standards or national standard. In Accordance, the graduate standard with BNSP, to enter the business world and industry, we already have equality both nationally and internationally.